Socio-demographic and clinical characteristics of complex febrile seizure and its association with abnormal electroencephalography - Hashim, Mohd Iftitah (2017)
Introduction: Febrile seizures were the commonest convulsive event during childhood. Currently there is no role of electroencephalography (EEG) study in simple febrile seizure. The precise role of EEG in evaluation of patients with complex febrile seizures (CFS) has not been established. In view of increased risk of future epilepsy in these patients, this study determines and to investigate the socio-demographic and clinical characteristics of CFS and its associations with an abnormal EEG outcome. Methods: All available EEG records at Hospital Universiti Sains Malaysia (HUSM) were retrospectively reviewed to identify those EEGs performed for the indication of febrile seizure (January 2005 to December 2015). From this cohort, those patients fulfilling criteria of CFS were selected. The association between socio-demographic, clinical characteristic and abnormal EEG was analysed. Results: A total of 77 patients were selected into the study. Of these, 14 patients (18.2%) had abnormal EEG. The mean age was 34.36±26.28 months, 46 were boys (59.7%) and 31 were girls (40.3%) and most of them were Malay (96.1%). All patients had normal neurological assessment post seizure. With multivariate analysis, frequency of seizure more than 2 episodes within 24-hour was significantly associated to abnormal EEG as compared to one episode of seizure (AOR 4.01, 95% CI 1.02-15.59, p=0.046).Conclusions: The seizure frequency of more than 2 episodes within 24-hour was an important predictor of abnormal EEG and should be an indication for EEG study among CFS patients. This group of patients warrant for further follow-up and monitoring for recurrence of seizure or epilepsy later.